The GPR-based estimation of the volumetric ice content of dispersed ground in the Central Yakut lowland - L. G. Neradovsky (Лëд и снег, 2019)
The previously unknown dependence between the volume ice content of frozen dispersed soils and their radiophysical properties (the speed of propagation and specific attenuation of the amplitude of electromagnetic waves) was studied in the layer of annual heat flows of Central Yakutia. The correlation between these characteristics determined in the laboratory and the method of discrete georadiolocation is established. The peculiarity of the connection is the sharp decline in the sensitivity of the propagation speed and the specific attenuation of electromagnetic waves in frozen dispersed soils with high volume ice content (more than  60%). In general, the specific attenuation of electromagnetic waves is more responsive to the change in the volume of ice content of frozen dispersed soils and, thus, it is more preferable to solve the problem of quantitative evaluation of this characteristic. The  proposed method of reusable measurements of signals of georadiolocation with changing position and azimuth of antennas of georadars in the vicinity of the network points of geological and geophysical observations allows to estimate the average values of the propagation speed and specific attenuation of electromagnetic waves with an error of not more than 10%. Due to this, according to the equations of logistic functions it is possible to calculate the average values of volume ice content with an error of 7–11%. With this error, the picture of the probability distribution according to the georadiolocation values of the volume ice content in the averages is completely identical to the laboratory data. On this basis, the found regression equations are recommended to be used for the calculation of the speed of propagation and specific attenuation of electromagnetic waves of background or average values of the volume ice content of frozen dispersed soils of the annual heat transfer layer in any part of the ice complex of the Central Yakut  lowland.